PKM Seminar Parenting Tangguh Di Era Milenial untuk Ibu Persit Kartika Chandra Kirana Makassar - Farida Aryani; Muhammad Rais; Fitriana Fitriana; Inayah Ridhayanti Qarimah; Maslina Maslina (INOVASI: Jurnal Hasil Pengabdian Masyarakat, 2025)
Abstract. The rapid development of digital technology has transformed parenting paradigms, presenting new complexities for parents guiding children amidst a plethora of information and digital content. This study highlights the urgency of adequate preparation for parents, particularly members of Persit Kartika Chandra Kirana (the Indonesian Army Wives Association) within the military environment, who face unique challenges related to their husbands' dynamic professions. Initial observations in Makassar indicated a gap in emotional support due to these dynamics, potentially affecting psychological well-being and the quality of childcare. The concept of "Resilient Parenting," encompassing emotional resilience, effective family communication, fostering child independence, and optimizing support systems, becomes essential in this context. This research outlines the implementation of a community service program in the form of a seminar titled "Becoming Resilient Parents in the Digital Era," involving 200 Persit members in Makassar City. Utilizing an interactive seminar approach that combined comprehensive material presentations, brainstorming sessions, and open discussions, the program aimed to enhance the parenting capacity of Persit members. The results indicate a significant improvement in participants' understanding of digital parenting literacy, the application of positive discipline, and assertive communication strategies. The discussion correlates these findings with Urie Bronfenbrenner's Ecological Systems Theory, emphasizing how interventions at the family microsystem level can mitigate the impacts of the digital macrosystem and military exosystem. This program successfully equipped participants with practical skills and strengthened community support networks, contributing to enhanced family resilience and the quality of child development in the digital era. Keywords: Resilient Parenting; Childrearing, Family Resilience, Digital Literacy.